Embedding Computational Thinking in STEM Education: A Comprehensive Literature Review - Novia Novia; Fandi Surya Wirawan; Supriyadi Supriyadi (CV. Dharma Samakta Edukhatulistiwa, 2025)
The study of incorporating computational thinking (CT) into science, technology, engineering, and mathematics (STEM) education has gained interest. We carried out a semi-systematic review of 50 empirical papers on this topic. Our findings highlighted the following crucial points: (a) the majority of research utilized domain-general descriptions for CT, while a few studies suggested domain-specific terms that addressed STEM education; (b) problem-based instruction developed as the most common teaching approach, with popular contextual topics including game design, robotics, and computational modelling; (c) assessments of student learning in combined CT and STEM varied in objectives and formats, with approximately one-third evaluating both CT and STEM integration. Based on our findings, we make recommendations for future study and implementation, with an emphasis on defining and evaluating CT in STEM contexts, developing successful instructional strategies for incorporating CT into STEM, and investigating approaches to promote inclusiveness in integrated CT and STEM education.